Integrating Blockchain Technology to Safeguard and Authenticate Cultural Heritage in the National Library - Jadallah, Nura Ali Hassan (Journal of Posthumanism, 2025)
The paper suggests a blockchain model to protect and verify digital cultural heritage resources in one of the national libraries. The framework guarantees the provenance, authenticity and safe preservation of the blockchain-limited artifacts, including manuscripts, rare books and works of art, by exploiting the decentralized, impossible to delete and transparent qualities of the blockchain. The prototype built in Python portrays the viability of inserting the metadata of artifacts on a personal blockchain. The study overcomes the problems of data tampering and loss, unauthorized access to data and follows the world trend of digitalization of cultural assets. The findings reveal that blockchain boosts confidence and effectiveness in handling cultural collection, and provides a scalable paradigm to national libraries. The paper provokes the field of blockchain in heritage science with its policy implications.